Postural Changes in Relation with Mismatched School Furniture - Nikki Indah Andraini (FAKULTAS SENI RUPA DAN DESAIN - UNIVERSITAS TARUMANAGARA, 2021)
Majority pupils who entered the school are in the perfect posture, however, after them graduates from elementary school, their Postural changes caused by an inappropriate postural habit during the period of stay in school. In 2018, U.S. Department of Education, National Center for Education Statistic conducted a survey and statistic number of instructional days and hours in the school year found that pupils spend 1080 hours their time at school or about 180 days/40 weeks per year. Based on literature, this article seeks to investigate mismatched school furniture impacted to deformities posture. Topics like Antropometric, Ergonomic, sitting posture and musculoskeletal disorder are investigated. The article concludes with insight important to have in mind when designing integrated school furniture.Keyword : Musculoskeletal disorder, School Furniture, School sitting posture, Anthropometric, Ergonomic